Blestriarene C exerts an inhibitory effect on triple-negative breast cancer through multiple signaling pathways - An, Junsha; Han, Mingyu; Tang, Hailin; Peng, Cheng; Huang, Wei; Peng, Fu (Frontiers in Pharmacology, 2024)
Introduction Breast cancer is the most common cancer worldwide, the leading cause of cancer death in women, and the fifth leading cause of cancer death. Triple negative breast cancer (TNBC), with high metastasis and mortality rates, is the most challenging subtype in breast cancer treatment. There is an urgent need to develop anti-TNBC drugs with significant efficacy, low side effects and good availability. In early drug screening, blestriarene C was found to have inhibitory effects on TNBC cells. In this article, we further explore the mechanisms associated with blestriarene C for breast cancer. Methods In this article, we take the approach of network pharmacology combined with in vivo and in vitro experiments. Network pharmacology analysis was used to predict the active components in Baiji, and to investigate the hub targets and related mechanisms of BC in TNBC treatment. The mechanism of anti-TNBC in vitro was evaluated by CCK-8 assay, cell apoptosis and cell cycle assays, wound healing assay, WB assay, and molecular docking analysis. The inhibition effect in vivo was test in subcutaneous tumor models established in mice. Results Through network pharmacology analysis and experiments, we screened out BC as the main active ingredient, and found that BC could inhibit the Ras/ERK/c-Fos signaling pathway while downregulating the expression of HSP90AA1 and upregulating the expression of PTGS2, thereby promoting apoptosis, causing S-phase cycle arrest, and inhibiting the proliferation and migration of BT549 cells. The in vivo results illustrated that BC inhibited the growth of TNBC tumors and has a high safety profile. By integrating network pharmacology with in vitro and in vivo experiments, this study demonstrated that BC inhibited the proliferation and migration of TNBC cells by inhibiting the Ras/ERK/c-Fos signaling pathway, promoting apoptosis, and causing S-phase cycle arrest. Discussion This study provides new evidence for the use of BC as a novel drug for TNBC treatment.